Influence of microstructural variations on morphology and separation properties of polybutadiene-based polyurethanes. Issue 25 (26th April 2021) - Pournaghshband Isfahani, Ali; Shahrooz, Mahdi; Yamamoto, Takuma; Muchtar, Ansori; Ito, Masateru M.; Yamaguchi, Daisuke; Takenaka, Mikihito; Sivaniah, Easan; Ghalei, Behnam
Abstract : Polybutadiene-based polyurethanes with different 1, 2-vinyl, cis, and trans contents were synthesized. The correlation between the gas transport properties and phase behaviors reveals their tunable molecular separation for designing gas membranes. Abstract : Polybutadiene-based polyurethanes with different cis / trans /1, 2-vinyl microstructure contents are synthesized. The phase morphology and physical properties of the polymers are investigated using spectroscopic analysis (FTIR and Raman), differential scanning calorimetry (DSC), X-ray scattering (WAXD and SAXS) and atomic force microscopy (AFM). In addition, their gas transport properties are determined for different gases at 4 bar and 25 °C. Thermodynamic incompatibility and steric hindrance of pendant groups are the dominant factors affecting the morphology and properties of the PUs. FTIR spectra, DSC, and SAXS analysis reveal a higher extent of phase mixing in high vinyl-content PUs. Moreover, the SAXS analysis and AFM phase images indicate smaller microdomains by increasing the vinyl content. Smaller permeable soft domains as well as the lower phase separation of the PUs with higher vinyl content create more tortuous pathways for gas molecules and deteriorate the gas permeability of the membranes.